Efektivitas Penggunaan Media Boneka Tangan Terhadap Keterampilan Bercerita Siswa Kelas V Sekolah Dasar - Rahmatilah, Farihatul; Supratno, Haris; Asmarani, Ratih (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
The use of instructional media is a creative learning activity that students enjoy doing. The purpose of this study is to describe (1) the learning process of using hand puppet media of storytelling skills, (2) student responses on learning using hand puppet media, (3) the result of storytelling skills by using hand puppet media. The research is a qualitative and quantitative research design. Qualitative design is emphasizing more attention on a